DOI: 10.11606/d.85.2016.tde-22012016-151851
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da remoção de Sr<sup>2+</sup> de soluções aquosas utilizando fibras de coco bruta e ativada com peróxido de hidrogênio em meio básico

Abstract: This work presents the potential of strontium ions removal from aqueous solutions using coconut fiber in raw and treated form with hydrogen peroxide, 1% and 4%, in alkaline conditions. The biosorption experiments were performed in batch mode with 2 mg.L-1 solution of Sr(NO 3) 2 and the influence of the following parameters were studied: contact time and pH. It was also evaluate the biosorption efficiency of the treated coconut fibers in comparison with the raw coconut fiber (RCF). The fibers characterizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The ability of the HC, CL, and CEL fibers to adsorb nitrogen (NH 4 + ), phosphorous (H 2 PO 4 -), and potassium (K + ) nutrients were systematically investigated by aqueous adsorption studies adapted from a previously reported method. 50 Briefly, each SCB derivative (50 mg) was put into 100 mL of multi-element solution at 10 mg L -1 of NH 4 + , H 2 PO 4 -, and K + ions with vigorous shaking at pH 3.5. This process was conducted at varying ions-substrate contact times (10-60 min) to find the optimal time condition for the saturated adsorption.…”
Section: Adsorption Capability Of the Scb Derivativesmentioning
confidence: 99%
“…The ability of the HC, CL, and CEL fibers to adsorb nitrogen (NH 4 + ), phosphorous (H 2 PO 4 -), and potassium (K + ) nutrients were systematically investigated by aqueous adsorption studies adapted from a previously reported method. 50 Briefly, each SCB derivative (50 mg) was put into 100 mL of multi-element solution at 10 mg L -1 of NH 4 + , H 2 PO 4 -, and K + ions with vigorous shaking at pH 3.5. This process was conducted at varying ions-substrate contact times (10-60 min) to find the optimal time condition for the saturated adsorption.…”
Section: Adsorption Capability Of the Scb Derivativesmentioning
confidence: 99%